Geometric and Numerical Foundations of Movements - Laumond, Jean-Paul.; Mansard, Nicolas; Lasserre, Jean-Bernard.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book aims at gathering roboticists, control theorists, neuroscientists, and mathematicians, in order to promote a multidisciplinary research on movement analysis. It follows the workshop (3z (BGeometric and Numerical Foundations of Movements (3y (Bheld at LAAS-CNRS in Toulouse in November 2015[1]. Its objective is to lay the foundations for a mutual understanding that is essential for synergetic development in motion research. In particular, the book promotes applications to robotics --and control in general-- of new optimization techniques based on recent results from real algebraic geometry.s
Keywords: EXTC Engineering; Geometry; Neurosciences; Numeric Computing